Towards harmonized methodologies in veterinary clinical bacteriology– outcomes of a European survey - Timofte Dorina, Cvetkovikj Iskra, Zendri Flavia...and Damborg Peter (ICOHAR, 2023)
Introduction: Veterinary microbiological diagnostic laboratories (VMDLs) play a key role in antimicrobial stewardship by providing guidance for antimicrobial treatment and by contributing to AMR surveillance. Methods: The European Network for Optimization of Veterinary Antimicrobial Treatment (ENOVAT) has designed and distributed a survey aiming to map diagnostic methodologies across VMDLs in 34 European countries. The survey focused on practices and interpretive criteria used for bacteriological culture and identification (C&ID), and antimicrobial susceptibility testing (AST) of animal bacterial pathogens. Results: A total of 290 laboratories responded, representing a mixture of academic (39%), governmental (33%), and private (28%) laboratories. Average C&ID turnaround varied from 1-2 days (78%) to 3-5 days (20%), and 6-8 days (0.5%) with similar timeframes for AST. Biochemical ID systems (e.g., API kits) were the most used (56%), followed by MALDI-TOF MS (46%). For AST, Kirby-Bauer disc-diffusion (DD) and MIC determination were conducted by 44% and 33% of laboratories, respectively. A combination of EUCAST and CLSI clinical breakpoints (CBPs) was the most common approach for interpretation of both DD (41%) and MIC (47%), whilst in some countries (i.e., France) national guidelines were used. Fifty three percent of laboratories used human CBPs for AST interpretation when veterinary breakpoints are lacking. Furthermore, 48% and 46% of VMDLs routinely screened isolates for methicillin resistance and ESBL production, respectively. Conclusions: A broad variety of methodologies were identified for C&ID and AST in European VMDLs, which emphasizes the need to harmonise diagnostic methodologies to benefit rational antimicrobial use and ultimately improve animal and public health